The making of middle/brow culture - Rubin, Joan Shelley, 1947- (University of North Carolina Press, 1992)
The proliferation of book clubs, reading groups, "outline" volumes, and new forms of book reviewing in the first half of the twentieth century influenced the tastes and pastimes of millions of Americans. By examining both the form and content of this popularization of literature, Joan Rubin recaptures here an activity that brought the humanities to the general public on an unprecedented scale. In doing so, she provides the first comprehensive analysis of the rise of American middlebrow culture and the values encompassed by it. Exploring the democratization of culture in a consumer society, Rubin concentrates on five important expressions of the middlebrow: the establishment of book clubs, including the founding of the Book-of-the-Month Club; the beginnings of "great books" programs; the creation ofthe New York Herald Tribune's book-review section; the popularity of such works as Will Durant's The Story of Philosophy; and the emergence of literary radio programs. Rubin also investigates the lives and expectations of the individuals who shaped these middlebrow enterprises--such figures as Stuart Pratt Sherman, Irita Van Doren, Henry Seidel Canby, Dorothy Canfield Fisher, John Erskine, William Lyon Phelps, Alexander Woollcott, and Clifton Fadiman. By demonstrating that an emphasis on character, liberal learning, and aesthetic training at least partly animated many of these writers, she revises the conventional view that the genteel tradition in American letters had vanished by World War I. Moreover, as she pursues the significance of these cultural intermediaries who connected elites and the masses by interpreting ideas to the public, Rubin forces a reconsideration of the boundary between high culture and popular sensibility
Spine title: The making of middlebrow culture.
Keywords: Books and reading -- United States -- History -- 20th century.; Literature -- Appreciation -- United States -- History -- 20th century.; Art appreciation -- United States -- History -- 20th century.; Popular culture -- United States -- History -- 20th century.; Middle class -- United States -- History -- 20th century.; Self-culture -- History -- 20th century.; Books and reading.; Self-culture.; Art appreciation.; Literature; Livres et lecture.; Littérature.; Art -- Appréciation.; Autodidaxie.; Culture populaire -- États-Unis -- Histoire -- 20e siècle.; Littérature -- Appréciation -- États-Unis -- Histoire -- 20e siècle.; Art -- Appréciation -- États-Unis -- Histoire -- 20e siècle.; Classes moyennes -- États-Unis -- Histoire -- 20e siècle.; Autodidaxie -- Histoire -- 20e siècle.; LITERARY CRITICISM -- Books & Reading.; Art appreciation; Books and reading; Literature -- Appreciation; Middle class; Popular culture; Self-culture; United States; Leesgewoonten.; Populaire literatuur.; Art -- Appréciation -- États-Unis -- 20e siècle.; Culture populaire -- États-Unis -- 20e siècle.; Livres et lecture -- États-Unis -- 20e siècle.; États-Unis -- Culture populaire -- 20e siècle.; 1900-1999; Art -- United -- History -- 20th century; Books -- United -- History -- 20th century; Literature -- Appreciation -- United -- History -- 20th century; Middle -- United -- History -- 20th century; Popular -- United -- History -- 20th century; Self-culture -- History -- 20th century; History